State of the digital age: modeling of institutional transformations - D. V. Shelokov (Цифровая социология)
The state is a complex social entity that plays a system-forming role in society. This is reflected in the implementation of many functions inherent in the state as a social institution. Their combination implies a directed influence on the elements that interact in a certain situation, in order to achieve goals in the most effective ways. Such goals seem significant in the context of a certain set of socially useful aspects of life. The implementation of public administration in such conditions actualizes its social orientation, which is based on a scientific approach using modern information and communication digital technologies. This approach should be based on social modeling, which is a specific way of knowing the corresponding aspect of being. Its specificity lies not only in the formalization of knowledge about social structures and processes, but also in the reflection of controlled and spontaneous processes, the awareness of the necessary actions and the will to carry them out in the interacting subjects – actors and building by them of a logically related model of behavior. At the same time, a feature of cognition is the maximum approximation of the formed image to a real process or phenomenon. This is achieved by taking into account the largest number of factors in their relationship with each other, as well as goals of creating the model and the results expected from its implementation. Within the framework of social modeling, there are objective ways to form a behavioral image that allow you to predict the direction and content specifics of the development of many social processes. The article considers the main areas of application of social modeling in public administration: assessment of the effectiveness of management bodies in the monitoring mode, development of strategic decisions, their translation into technological formats, digital representations of strategies and technologies.